An Investigation Into The Effects Of Parental Involvement And Reading Attitudes On Reading Ability Of Efl Students In The Sultanate Of Oman Basic Education Schools - Al Bahri, Harith Nasser Khalaf (2021)
The present study examined Omani Cycle One Basic Education EFL students’ reading ability in relation to their gender, reading attitudes, parental involvement, parental education and income level. Additionally, the present study also explored the challenges students faced in reading.